Tezepelumab can Restore Normal Lung Function in Patients with Severe, Uncontrolled Asthma: Pooled Results from the PATHWAY and NAVIGATOR Studies - Ian D. Pavord; Christopher E. Brightling; Stephanie Korn; Nicole L. Martin; Sandhia S. Ponnarambil; Nestor A. Molfino; Jane R. Parnes; Christopher S. Ambrose (Pulmonary Therapy)
Abstract Introduction This post hoc analysis assessed the ability of tezepelumab treatment to restore normal lung function in patients with severe, uncontrolled asthma with abnormal lung function at baseline pooled from the PATHWAY and NAVIGATOR studies. Methods PATHWAY and NAVIGATOR were multicentre, randomized, double-blind, placebo-controlled studies. Patients (12–80 years old) included in this analysis received tezepelumab 210 mg subcutaneously every 4 weeks or matched placebo for 52 weeks. Patients had a percent predicted pre-bronchodilator (BD) forced expiratory volume in 1 s (FEV1) of < 80% (< 90% for adolescents in NAVIGATOR) at screening. The change from baseline to week 52 in pre-BD FEV1 was assessed by baseline percent predicted pre-BD FEV1 subgroup [abnormal (< 80%) and normal (≥ 80%)]. The proportion of patients with abnormal lung function at baseline who achieved normal lung function at week 52 was assessed overall and by biomarker level and disease duration subgroups. Results Of the 665 and 669 patients who received tezepelumab or placebo, respectively, 564 and 569 had abnormal lung function at baseline. Tezepelumab improved the pre-BD FEV1 from baseline to week 52 versus placebo by 0.14 L [95% confidence interval (CI) 0.09–0.19] and 0.13 L (95% CI 0.01–0.24) in patients with abnormal and normal lung function at baseline, respectively. A higher proportion of tezepelumab than placebo recipients with abnormal lung function at baseline achieved normal lung function at week 52 (17.2% vs. 9.9%, respectively). Among tezepelumab recipients, those with higher levels of type 2 inflammatory biomarkers and a shorter duration of disease at baseline were more likely to achieve normal lung function at week 52. Conclusion In patients with severe, uncontrolled asthma, a greater proportion of tezepelumab than placebo recipients with abnormal lung function at baseline achieved normal lung function at week 52. Trial Registration PATHWAY: NCT02054130; NAVIGATOR: NCT03347279.